2015
DOI: 10.14814/phy2.12624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of imperceptible vibratory noise applied to wrist skin on fingertip touch evoked potentials - an EEG study

Abstract: Random vibration applied to skin can change the sense of touch. Specifically, low amplitude white-noise vibration can improve fingertip touch perception. In fact, fingertip touch sensation can improve even when imperceptible random vibration is applied to other remote upper extremity areas such as wrist, dorsum of the hand, or forearm. As such, vibration can be used to manipulate sensory feedback and improve dexterity, particularly during neurological rehabilitation. Nonetheless, the neurological bases for rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…Seo et al [98] provided a more direct explanation. They investigated the influence of imperceptible vibrotactile noise on the wrist, as used in the current study, on somatosensory evoked potential of fingertip touch [98].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seo et al [98] provided a more direct explanation. They investigated the influence of imperceptible vibrotactile noise on the wrist, as used in the current study, on somatosensory evoked potential of fingertip touch [98].…”
Section: Discussionmentioning
confidence: 99%
“…Seo et al [98] provided a more direct explanation. They investigated the influence of imperceptible vibrotactile noise on the wrist, as used in the current study, on somatosensory evoked potential of fingertip touch [98]. As a result, the peak-to-peak somatosensory evoked potentials of the sensorimotor cortex were significantly increased by imperceptible vibrotactile noise (SR on) compared to the absence of vibrotactile noise (SR off) [98].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies applying sub-threshold tactile stimulation, the resulting stimulation amplitudes were usually not reported (Priplata et al, 2002;Collins et al, 2003;Seo et al, 2014Seo et al, , 2015Stephen et al, 2014;Dettmer et al, 2016). However, this information is an important requirement for future study designs.…”
Section: Stimulation Amplitudes Are Consistent With Previous Findingsmentioning
confidence: 99%
“…To gain a better understanding of the mechanisms involved when stochastic stimulation is applied to different body sites, further studies using kinematic outcome measures, EEG or MRI imaging are required, especially when the upper extremities are concerned. In contrast to electromagnetic tactors frequently used in previous studies (Priplata et al, 2006;Ribot-Ciscar et al, 2013;Ross et al, 2013;Seo et al, 2014Seo et al, , 2015, the pneumatic stimulator developed for this study is compatible with MRI systems and therefore ideal for such future experiments.…”
Section: Stimulation Amplitudes Are Consistent With Previous Findingsmentioning
confidence: 99%
“…Improved signal detection by weak noise input has been studied not only in the field of physical events but also in biological systems, including human sensory systems [14 -16]. In the human somatosensory system, touch sensation of the hand can be enhanced by weak vibrotactile noise [6,12,17]. Collins and colleagues found that detection of a touch stimulus to the hand improved when vibration noise was added to the touch stimulus.…”
Section: Experiment-2mentioning
confidence: 99%